Antioxidant Activities in Germinating Mungbean - Irvia Resti Puyanda; Uyun Nurul Aini (P3M Institut Teknologi Pagar Alam, 2023)
The objectives of this work were to investigate the influence of germination times (24,48, 72, 96, 120 h) and conditions (light and dark) on the moisture content and antioxidant activity in mungbean sprout. The antioxidant activity were analyzed using in vitro methods. ABTS and DPPH methods were used to measure the antioxidant activity. A significant increase (p-value < 0.05) was observed under ABTS method at 72 and 96 h, while it decreased at longer germination times. In addition, using DPPH method decreased the antioxidant activity significantly (p-value < 0.05) from 24 to 48 h, however, it increases again at 72 and 96 h. Germination times and conditions significantly affects (p-value < 0.05) the antioxidant activities of mungbean sprout. Based on the results, germination under dark conditions enhanced lower antioxidant activities during germination process.